From knowledge trees to rhizomes and rukus: plant metaphors in the relational organization of knowledge: plant metaphors in the relational organization of knowledge (Advances in Knowledge Representation, 2022)
The tree has been used as a key metaphor, since the Middle Ages, to depict knowledge representation systems. However, the contemporary socio-technical context demands considerations that admit other representations of the ways in whichknowledge is produced, organized, and represented. In this sense, the purpose of this textis to reflect on arboreal images used historically as representational symbols of knowledgestructures and, furthermore, to conjecture, within the scope of the transversal discussionsthat involve the plane of sociobiodiversity involved in the production of knowledge, aboutsome of these representations used in different contexts and times. In the end, we arrive atthe representation of the Rhizome proposed by G. Deleuze and F. Guatari, the Baniana treeby S. Ranganathan, and the Ruku tree, represented in the painting "The descent of theJenipapo shaman from the kingdom of medicines", (2021), produced by the Makuxiindigenous artivist Jaider Esbell. The final considerations suggest that by broadening ourunderstanding of the tree as a representation of relationships and not of dichotomies orhierarchies, we will be able to perceive, with more equity, the social, plural andcosmological arrangements of knowledge.